Penggunaan Media Bahan Alam untuk Meningkatkan Penalaran Matematis Anak Usia 5-6 Tahun - Siti Chodijah (Perkumpulan Kualitama Edukatika Indonesia, 2021)
Mathematical reasoning is a part of mathematical thinking which includes making generalizations and drawing valid conclusions about ideas and how these ideas are related. If problem solving plays a central role in mathematics, then reasoning appears to play a similar role in problem solving. In playing so that children can explore play activities related to mathematics, they can use natural media media that are around our environment such as stones, leaves, shells, twigs, flowers. In the use of natural media media to improve the mathematical reasoning of children aged 5-6 years by classifying shapes, sizes, measuring, counting, counting. This research uses qualitative research methods. Qualitative research is research on descriptive research and tends to use analysis. Process and meaning (subject perspective) are more highlighted in qualitative research. Activities carried out to be observed include counting activities with shells, counting with twigs, introduction of geometric shapes with stones and shells with AB-AB patterns. Based on the data obtained in the field through the observations of students when playing like the variety of games above and conducting interviews with the teachers. That the ability of children to do mathematical reasoning can be grouped into children who have started to develop (MB) 64%, children who have developed as expected (BSH) 25% and children who have developed very well (BSB) 11%. This can be seen in the pie chart 1.1 The mathematical reasoning ability of children aged 5-6 years in several kindergartens in Pekalongan City. Mathematics learning is important for children who follow Early Childhood Education. This is because mathematics can develop children's cognitive abilities and as a preparation for mathematics skills at the next level of education.